Development of Digital Teaching Materials Based on Guided Inquiry With A Multirepresentation Approach to Improve Conceptual Understanding of Buffer - Nabiila Yumna Taqiyya; Munzil Munzil; Erti Hamimi; Hanumi Oktiyani Rusdi (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Students' difficulties in understanding buffer solution concepts are attributed to limited chemical representation skills and learning models that provide insufficient opportunities for active learning. The purpose of this study is to develop digital teaching material, test their validity, and determine their effectiveness in improving students’ conceptual understanding of buffer solutions. This study is research and development (R&D) using the 4D development model (define, design, develop, disseminate). Data were collected through interviews and validation questionnaires on media, content, and conceptual accuracy, teacher and student readability, and conceptual understanding tests. The validation test results showed an average percentage of 84.71% (valid), while the student readability test showed 86.78% (very good). The teaching materials were tested through quasi-experimental research with a posttest-only design with non-equivalent groups. The mann-whitney test results for the posttest scores showed a Sig. (2-tailed) value of 0.005, the effect size analysis result is 0.828, and the percentage of conceptual understanding of the experiment class is 93.10%. The research results show that the teaching materials are valid and effective in improving students' conceptual understanding of buffer